ANALISIS NILAI MORAL DAN NILAI SOSIAL DALAM NOVEL SEJARAH MAJAPAHIT BALA SANGGRAMA KARYA LANGIT KRESNA HARIADI SEBAGAI BAHAN PEMBELAJARAN BAHASA INDONESIA DI SMA - Sopyan Sauri; Trisnawati Trisnawati; Siti Mutmainah (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
This study aims to determine the moral and social values contained in the historical novel Majapahit Bala Sanggrama by Langit Kresna Hariadi. As well as to determine the effectiveness as a literary learning material in teaching Indonesian. The research was carried out using qualitative research methods. Data collection techniques used reading techniques and note-taking techniques. The data analysis technique used descriptive analytic technique. The results of data analysis on the historical novel majapahit bala sanggrama by Langit Kresna Hariadi are the moral values contained in the historical novel, namely determination, longing, restlessness, oscillation between several choices, fear, revenge, disappointment, caring for others, respect for others, not forcing will, conspire, have good prejudice, pray, surrender to God, trust in God. The social values contained in the historical novel are devotion, mutual assistance, kinship, loyalty, care, belonging, discipline, empathy, tolerance and cooperation. The results of the analysis of moral values and social values in the historical novel majapahit bala sanggrama by Langit Kresna Hariadi can be used as an alternative material for learning Indonesian in high school.